Effect of different extraction methods towards biodiesel production from chlorella vulgaris - Shanthini, Murugu (2025)
The best alternative fuels for the future are biofuels made from algal biomass since microalgae biomass can store lipids in their cells similarly to vegetable oils, potentially producing 100 times more oil per acre than any other plant. Lipid can be extracted from microalgae using either a mechanical or chemical approach. The chemical techniques for extracting lipids include Soxhlet extraction, Ultrasonication, One-Step direct Tranesterification and Homogenizer. The various techniques for removing lipids or oils from microalgae biomass in order to produce biodiesel are reviewed in this research. Pretreatment procedures like ultrasonication and, in addition to solvent, have been shown to enhance the yield of lipid extraction from microalgae. Out of four extraction methods, Ultrasonnication is best method to extract lipidUltrasonication proved to be the most effective extraction method, yielding the highest variety of fatty acids, including methyl arachidate, with prominent peaks observed at retention times between 24.507–28.364 and 30.209–31.352 minutes. One-step transesterification produced fewer fatty acids, primarily methyl trans-9,12 linolelaidate, palmitic acid, and stearic acid. Soxhlet extraction resulted in only one fatty acid being detected, while the homogenizer method yielded no fatty acids, demonstrating its ineffectiveness for lipid extraction.The predominant fatty acids in the biodiesel samples were C16 and C18 chains, which are critical for biodiesel quality as they influence cetane number, oxidative stability, and cold flow characteristics. Ultrasonication was identified as the most efficient method, while Soxhlet extraction's high-temperature process caused lipid degradation, and the homogenizer failed to disrupt cells effectively for lipid extraction.